Channel base current effects on the magnetic flux density waveshape associated with vertical lightning channel - Ab Kadir, Mohd Zainal Abidin; Gomes, Chandima; Wan Ahmad, Wan Fatinhamamah (2012)
The electromagnetic fields due to lightning channel are considered as effctive factors to induce voltage on the power systems. The shape of electromagnetic wave associated with lightning channel depends highly on return stroke current wave shape and the parameters of lightning channel and its geometry. This paper considered on the relation between channel base current parameters based on Heidler function as a realistic current function and the wave shapes of magnetic flux density. Furthermore, some general functions were proposed by considering their effects The results showed that the proposed equations are in very good agreement with the calculated values using direct methods They could also predict the magnetic flux wave shapes versus different channel base current parameters under similar geometrical and lightning channel conditions. The estimated magnetic flux density waveshapes can be applied to Rachidi model for evaluation of the induced voltage due to indirect strike.